The Study of the Structure-Diuretic Activity Relationship in a Series of New N-(Arylalkyl)-6-hydroxy-2-methyl-4-oxo-2,4-dihydro-1H-pyrrolo-[3,2,1-ij]quinoline-5-carboxamides - Igor V. Ukrainets; Mykola Y. Golik; Lyudmila V. Sidorenko; Valentina I. Korniyenko; Lina A. Grinevich; Galina Sim; Olga V. Kryvanych (MDPI AG, 2018)
In accordance with the principles of “me-too” technique, the preparative method for obtaining has been proposed, and the synthesis of a large series of new N-(arylalkyl)-6-hydroxy-2-methyl-4-oxo-2,4-dihydro-1H-pyrrolo[3,2,1-ij]quinoline-5-carboxamides as structurally close analogs of tricyclic pyrrolo- and pyridoquinoline diuretics has been carried out. All target compounds were obtained with high yields and purity by amidation of ethyl ester of the corresponding 2-methyl-pyrroloquinoline-5-carboxylic acid with arylalkylamines in boiling ethanol. Their structure was confirmed by the data of elemental analysis, nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry and polarimetry. Moreover, interpretations of their 1H and 13C-NMR spectra, their mass spectrometric behavior, as well as peculiarities of the polarimetric studies were discussed. The effect of N-(arylalkyl)-6-hydroxy-2-methyl-4-oxo-2,4-dihydro-1H-pyrrolo[3,2,1-ij]quinoline-5-carboxamides on the urinary function of the kidneys was studied in white rats by the standard method of oral administration in the dose of 10 mg/kg compared to hydrochlorothiazide. According to the results of the primary pharmacological screening, the structural and biological regularities that were unexpected, but interesting for further studies were revealed. Among the substances studied, the samples, which by their diuretic effect are not inferior and even superior to both the known hydrochlorothiazide and the lead structure of the pyrroloquinoline group, have been found. On this basis, it can be argued that the introduction of the methyl group made by us in position 2 of pyrrolo[3,2,1-ij]quinoline nucleus can be considered as a successful and promising implementation of the “me-too” cloning of tricyclic 4-hydroxyquinoline-2-one diuretics.